2020
DOI: 10.3389/fnsyn.2020.588954
|View full text |Cite
|
Sign up to set email alerts
|

The Creatine Transporter Unfolded: A Knotty Premise in the Cerebral Creatine Deficiency Syndrome

Abstract: Creatine provides cells with high-energy phosphates for the rapid reconstitution of hydrolyzed adenosine triphosphate. The eponymous creatine transporter (CRT1/SLC6A8) belongs to a family of solute carrier 6 (SLC6) proteins. The key role of CRT1 is to translocate creatine across tissue barriers and into target cells, such as neurons and myocytes. Individuals harboring mutations in the coding sequence of the human CRT1 gene develop creatine transporter deficiency (CTD), one of the pivotal underlying causes of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 151 publications
0
32
0
Order By: Relevance
“…Future work will aim at further characterizing the molecular mechanism and the consequences of CTD in the Slc6a8 Y389C rat line both in periphery and in CNS. Recent work demonstrated that several variants of CrT are expressed although misfolded, some of them being rescued with chemical chaperones thus opening new avenues for the treatment of CTD patients 53 , 54 . Using the Slc6a8 Y389C rat line to develop new strategies of treatment for CTD, this chaperone approach will also be tested in this new in vivo model.…”
Section: Discussionmentioning
confidence: 99%
“…Future work will aim at further characterizing the molecular mechanism and the consequences of CTD in the Slc6a8 Y389C rat line both in periphery and in CNS. Recent work demonstrated that several variants of CrT are expressed although misfolded, some of them being rescued with chemical chaperones thus opening new avenues for the treatment of CTD patients 53 , 54 . Using the Slc6a8 Y389C rat line to develop new strategies of treatment for CTD, this chaperone approach will also be tested in this new in vivo model.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Cr is critical to promote antitumor activity in the cytotoxic T CD8 + cells, and the response to tumor challenge is severely impaired in KO(2-4) mice [183]. These results add up to the accumulating evidence that implicates CRT in cancer, encouraging a close survey of cancer incidence in CTD patients [128].…”
Section: Role Of Metabolism In Cancer Progression: Novel Insights From Creatine Modelsmentioning
confidence: 56%
“…Although locomotor activity was slightly increased in Nes-KO animals, it is unlikely that moderate hyperactivity could account for the observed cognitive dysfunction [102,125,126]. On the other hand, hyperactivity and attention deficits are commonly described in CTD patients [25,128]. Since hyperactivity in ubiquitous KO mice is presumably masked by the motor problems due to peripheral Cr deficiency, the presence of this phenotype in conditional mice represents an original finding, making them a viable model to study certain aspects of this disorder.…”
Section: Brain-and Cell-specific Conditional Mouse Modelsmentioning
confidence: 99%
“…Conformational changes of the CRT might trigger quality control mechanisms involving N-glycosylation (e.g., unfolded protein response) [ 191 ]. For a recent comprehensive review on this topic and novel therapeutic strategies related to Cr deficiency syndrome, please refer to [ 192 ].…”
Section: Discussionmentioning
confidence: 99%